Evaluation of the Sensititre system for quantitative antimicrobial drug susceptibility testing: a collaborative study. - Gavan, T L (1980)
This three-center collaborative study was conducted to evaluate samples of Sensititre antimicrobial microdilution panels (GIBCO/INVENEX). Sensititre minimum inhibitory concentrations of 27 bacterial isolates were compared with those obtained by a reference microdilution method. The Sensititre and microdilution minimum inhibitory concentrations were equivalent within +/- 1 dilution in 87.6% of the comparable test results. Intralaboratory reproducibilities of the Sensititre and microdilution endpoints were equivalent with 80.4 and 82.4%, respetively, of on-scale endpoints in absolute agreement. Sensititre was more reproducible among laboratories, with nearly a 10% greater agreement of triplicate results. The Sensititre microdilution test as evaluated gave results which were essentially equivalent to those obtained with a standardized microdilution method.